2009
DOI: 10.1080/00207540801930237
|View full text |Cite
|
Sign up to set email alerts
|

Integrated workforce capacity and inventory management under labour supply uncertainty

Abstract: In a manufacturing environment with volatile demand, inventory management can be coupled with dynamic capacity adjustments for handling the fluctuations more effectively. In this study, we consider the problem of integrated capacity and inventory management under non-stationary stochastic demand and capacity uncertainty. The capacity planning problem is investigated from the workforce planning perspective where the capacity can be temporarily increased by utilising contingent workers from an external labour su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…In their paper, Pac et al (2007) classified the production capacity under two main categories: permanent capacity and contingent capacity formed by the workers that can be acquired temporarily from what they call an External Labor Supply Agency (ELSA). Their paper investigates different supply uncertainty in ELSA responses to workforce request.…”
Section: Contingent Workforce: a Sourcing Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…In their paper, Pac et al (2007) classified the production capacity under two main categories: permanent capacity and contingent capacity formed by the workers that can be acquired temporarily from what they call an External Labor Supply Agency (ELSA). Their paper investigates different supply uncertainty in ELSA responses to workforce request.…”
Section: Contingent Workforce: a Sourcing Problemmentioning
confidence: 99%
“…Moreover, identifying the needs for contingent workers in the company, finding the right supplier, reducing the time for candidate sourcing, monitoring their presence, adapting their number to the level of demand, etc., are activities that can be supported and improved using supply and purchasing techniques. Pac et al (2007) identified the risk and wrote that, in case there is a high demand for contingent workers in the market at the time of the request, or if the manufacturer requires the workers in short notice, the risk of the request not being met in full terms is highter. They identified different risk factors such as the size of available temporary worker pool, capability of finding skilled workers, competition in the environment, demand structure of different customers, and opportunities in alternative options.…”
Section: Contingent Workforce: a Sourcing Problemmentioning
confidence: 99%
“…From Proposition B-4 of Heyman and Sobel (2004), coupled with the convexity preservation of affine mappings (see Hiriart-Urruty and Lemaréchal, 1993) it follows that the resulting g and h functions are convex when J is convex. Finally,…”
Section: Appendixmentioning
confidence: 99%
“…On the other hand, the effects of demand uncertainties and fluctuations do not only remain at the level of manufacturing enterprise, but also the entire supply chain which might lead to inefficient processes and non-value-creating activities throughout the supply chain [3], [4]. The warehouses and storage function are also inseparable parts of the supply chain as much as that of production activities in reducing the adverse effects of demand uncertainties in this context [5] and has a critical importance on the success of such activities [6].…”
Section: Introductionmentioning
confidence: 99%